THE FAMILIAR CONTEXT AND THE PERFORMANCE OF 5th GRADE STUDENTS FROM A SCHOOL IN THE INNER REGION OF SAO PAULO - Osti, Andreia [UNESP] (Univ Estadual Campinas, Fac Educacao, 2016)
This article analyzes the relationship between the family ambience, considering its material and human resources and school performance of primary school students. The sample consisted of 120 students from the 5th grade of a municipal school in the Metropolitan Region of Campinas, 60 of those students having satisfactory academic performance and 60 unsatisfactory performance, according to their teacher's evaluation. The instrument used to evaluate the human and material resources was a questionnaire about the backups and resources from the familiar ambience elaborated from the Resource Inventory of Home Ambience (RAF), applied collectively. The results indicate that there are differences between the groups in relation to human and cultural resources, as well as in family interaction and participation in the school. Overall, it can be affirmed that children with satisfactory school performance report having had greater access to extracurricular activities and greater opportunities of interaction with their parents. They also affirm having a preestablished routine in the house to accomplish the school activities. The group with unsatisfactory performance, in relation to all the categories described, presented lower rates. This work contributes to the understanding of the importance of family interaction for school performance, reflected in the possibilities of dialogue, to sharing a household activity and monitoring the child's learning process.
Keywords: Family; School Performance; Learning